Local Certification: Genetically Modified Organisms and Commercialization - Sujadmiko, Bayu; Tisnanta, HS; Melati Davey, Orima (Kertha Patrika; Vol 43 No 1 (2021), 2021)
Local government requires a regulatory framework as a base of Genetically Modified Organisms’ (GMO) development and expansion in order to support food sovereignty. In regions of Indonesia, GMO products could be strengthened through local certification. The involvement of the government is vital in supporting the economical activities of entrepreneurs in certain regions. Researchers are interested in further discussion on, “Local Certification: Genetically Modified Organisms’ Commercialization”. The studies focus on the urgency for local certification in GMO products and the commercialization of local certification towards GMO Products of region in Indonesia. This is normative research through a statute approach, which concerns legal basis for local government authority regarding agricultural products’ affairs. The research suggested that urgency for local certification in every region is very much needed to bolster food production with GMO technology base as part of the geographical index product. In the implementation amongst society, the product could be supervised and developed to enhance local and national economic activities by paying attention to the quality of genetically modified products and its food safety. GMO commercialization is still constrained by permit on feed, food and environmental safety. Therefore, the Indonesian Government’s protection on GMO product commercialization is required, both from national and local governments through a local certification. The practice upon food local certification is implemented in several regions of Indonesia, such as West Sumatra by establishing an institution; Kebumen Regency by forming a food certification related regulation and Palembang City also by applying food certification.